DESCRIPTION OF INDIVIDUAL CHARACTERISTICS IN NURSES: A STUDY ON THE NEEDLE EVENTS IN HOSPITAL X HOSPITAL BEKASI DISTRICT - Vionalita, Gisely; fitri br Nababan, Elisa; Alia Keumala Muda, Cut; Purno Wahyu, Ari (International Journal of Psychosocial Rehabilitation, 2020)
Accidents that often occur in health care are used needle puncture wounds used to inject patients. Nurses are the main category of healthcare professionals who are vulnerable to NSI. Needle Stick Injury (NSI) is an accident caused by needling that is contaminated with blood or body fluids of the patient. Impacts that can be caused by needle sticking include contracting the disease from an infected patient. The purpose of this study was to determine the description of the characteristics of individuals in nurses who experienced the incidence of needling in the inpatient room of the hospital in Bekasi district in 2017-2018. The research design used is a case series research design or case study, where all the observed variables are the variables that experienced a case of needling in the Inpatient Room of X Hospital in Bekasi district in 2017-2018. The results showed that the highest proportion of sex characteristics of nurses who experienced the incidence of needling in the highest inpatient room were female sex as many as 13 nurses (92.9%). The highest proportion of age characteristics is <30 years as many as 10 nurses (71.4%). The highest proportion of education characteristics of nurses who experienced the incidence of needling with S1 education was 8 people (57.1%). The highest proportion of the characteristics of the length of service of nurses who experienced the incidence of needling with a work period of <3 years is as many as 7 people (50%). The highest proportion of nurse respondents who experienced a pin prick was 9 nurses (65%) had not been trained on NSI.